Intonational Focus Marking by Syrian Arabic Learners of German: On the Role of Cross-Linguistic Influence and Proficiency - Zarah Kampschulte; Angelika Braun; Katharina Zahner-Ritter (Languages, 2025)
Acquiring prosodic focus marking in a second language (L2) is difficult for learners whose native language utilizes strategies that differ from those of the target language. German typically uses pitch accents (L+H*/H*) to mark focus, while (Modern Standard) Arabic preferably employs a syntactic strategy (word order) or lexical means. In Syrian Arabic, a variety which is predominantly oral, pitch accents are used to mark focus, but the distribution and types are different from German. The present study investigates how Syrian Arabic learners of German prosodically mark focus in L2 German. A question–answer paradigm was used to elicit German subject-verb-object (SVO)-sentences with broad, narrow, or contrastive focus. Productions of advanced (C1, N = 17) and intermediate (B1/B2, N = 8) Syrian Arabic learners were compared to those of German controls (N = 12). Like the controls, both learner groups successfully placed pitch accents on focused constituents. However, learners, especially those with lower proficiency, used more pitch accents in non-focal regions than the controls, revealing challenges in de-accentuation. These may result from the larger number of phrase boundaries in learners’ productions, which in turn might be explained by transfer from the L1 or aspects of general fluency. Learners also differed from the controls with respect to accent type. They predominantly used H* for narrow or contrastive focus (instead of L+H*); proficiency effects played only a minor role here. Our study hence reveals an intricate interplay between cross-linguistic influence and proficiency in the L2 acquisition of prosodic focus marking, targeting a language pair so far underrepresented in the literature (German vs. Syrian Arabic).